2022
DOI: 10.1007/s12028-022-01453-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Patients’ Characteristics, Provided Care, and Outcomes Following Spontaneous Intracerebral Hemorrhage

Abstract: Background Sex-related differences in patients with spontaneous, non-traumatic intracerebral hemorrhage (ICH) are poorly investigated so far. This study elucidates whether sex-related differences in ICH care in a neurocritical care setting exist, particularly regarding provided care, while also taking patient characteristics, and outcomes into account. Methods This retrospective single center study includes all consecutive patients with spontaneous ICH adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Similarly, our group recently reported that at our institution women with spontaneous intracerebral hemorrhage are less likely than men to receive an EVD despite comparable frequency of hydrocephalus/ventriculomegaly. Multivariate analysis proved male gender to be independently associated with EVD insertion in these patients even after correction for location and severity of bleeding [33].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, our group recently reported that at our institution women with spontaneous intracerebral hemorrhage are less likely than men to receive an EVD despite comparable frequency of hydrocephalus/ventriculomegaly. Multivariate analysis proved male gender to be independently associated with EVD insertion in these patients even after correction for location and severity of bleeding [33].…”
Section: Discussionmentioning
confidence: 90%
“…We previously reported that male patients with spontaneous intracerebral hemorrhage were almost three times as likely to receive an external ventricular drain (EVD) in comparison to women in the absence of radiographic or clinical differences. We suggested that a form of "gender-bias" might have influenced the decisionmaking process for the insertion of an EVD [33] The identification of sex-and gender-related differences in patients with aSAH is of great interest to evaluate the current monitoring and treatment strategies in order to offer a more personalized management and to better distribute the available resources. The aim of this study was to compare clinical characteristics, management, intensity of treatment, and outcome among males and females with aSAH.…”
Section: Introductionmentioning
confidence: 99%
“…Women in the FAST cohort were older than men and had a higher prevalence of premorbid hypertension (both statistically not significant) which might correlate with higher baseline comorbidities in women not recorded in the FAST trial. Women may have received less aggressive care 37 , or may have had a higher incidence of in-hospital complications. 37 38 Given that an age-dependent increased risk of poor outcomes in women has been reported, the overall younger age of the FAST participants compared to prior cohorts may explain discrepancies with prior studies as well.…”
Section: Discussionmentioning
confidence: 99%
“…Women may have received less aggressive care 37 , or may have had a higher incidence of in-hospital complications. 37 38 Given that an age-dependent increased risk of poor outcomes in women has been reported, the overall younger age of the FAST participants compared to prior cohorts may explain discrepancies with prior studies as well. 39…”
Section: Discussionmentioning
confidence: 99%
“…Some of the known risk factors for hematoma expansion include symptom onset to initial CT imaging, higher initial ICH volumes, concurrent antiplatelet and anticoagulant usage, and the presence of contrast extravasation on CTA, also known as the "spot sign” [ 13 , 14 ]. Of note, ICH volume is the strongest predictor of 30-day mortality regardless of hematoma location.…”
Section: Discussionmentioning
confidence: 99%